Corporate Governance and Corporate Performance: Tobin's Q Analysis on Financial Sector Companies on the Indonesia Stock Exchange - Rahman, Fadli; Tamala, Putri; Hanggraeni, Dewi (Syntax Corporation, 2025)
This study examines the effect of the corporate governance mechanism (insider shareholding, board size, and institutional ownership) on firm performance measured by Tobin’s Q in financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2023. Using a sample of 99 companies and secondary data from Bloomberg, the study employs multiple linear regression to analyze the relationship between governance variables and market performance. The results show that none of the three governance variables has a statistically significant effect on Tobin’s Q. These findings suggest that traditional internal governance mechanisms may not significantly influence firm market value in Indonesia’s financial sector context. The study contributes to the corporate governance literature by providing empirical evidence from a developing country and recommends exploring additional factors such as executive compensation and investor sentiment in future research.